Imprinting and expression of Dio3os mirrors Dio3 in rat - Dietz, William H.; Masterson, Kevin; Sittig, Laura J.; Redei, Eva E.; Herzing, Laura B. (Frontiers in Genetics, 2012)
Genomic imprinting, the preferential expression of maternal or paternal alleles of imprinted genes, is often maintained through expression of imprinted long noncoding (lnc) ‘antisense’ RNAs. These may overlap imprinted transcripts, and are expressed from the opposite allele. Previously we have described brain region-specific imprinted expression of the Dio3 gene in rat, which is preferentially modified by fetal ethanol exposure. The Dio3os (opposite strand) transcript is transcribed in opposite orientation to Dio3 in mouse and human, partially overlaps the Dio3 promoter, and mirrors total Dio3 developmental expression levels. Here, we present that the rat Dio3os transcript(s) exhibits brain region specific imprinted expression patterns similar to those of Dio3. Rat Dio3os transcript expression is also similarly modified by fetal ethanol exposure. Uniquely, both Dio3 and Dio3os expression occur on the same, rather than opposite, alleles, as determined by strand-specific RT-PCR. Future studies will require direct manipulation of the Dio3os transcript to determine whether the novel paralleling of total and allele-specific expression patterns of this sense/anti-sense imprinted gene pair reflects an as-yet undefined regulatory mechanism for lncRNA mediated tissue-specific imprinted expression, or rather is a consequence of a more straightforward, but previously undescribed transcriptional coregulation process.